Tržaški Separatist in münchenski Delovodja: podobnosti in razhajanja v pogledih Franca Jeze in njegovega sodobnika Branka Pistivška o ideji samostojne in neodvisne slovenske države - Hazemali, David (Dileme, 2025)
The authors analyse the ideological and political differences and similarities between Franc Jeza and Branko Pistivšek, two representatives of the Slovenian political emigration during the Cold War. Both Jeza, a shrewd strategist, and Pistivšek, a passionate cultural activist, advocated for Slovenian independence, but they used different methods in doing so. The discussion also sheds light on the role of the State Security Service (SDV), which systematically monitored both men and analysed their publications, perceiving them as a threat to the Yugoslav regime. The article thus simultaneously sheds light on the methodology of the secret political police's surveillance of émigré intellectuals, explores the background of the Action Committee for an Independent Slovenia (AONS), and identifies the key parameters used by the SDV to label hostile activity. In doing so, it provides insight into the broader repressive apparatus of the Yugoslav authorities, while examining how the political emigration shaped the discourse on Slovenian independence and dealt with internal divisions and external pressures.
Keywords: Jeza, Franc; neodvisnost Slovenije; SDV; Slovenian independence; Slovenian political emigration; slovenska politična emigracija; Služba državne varnosti; State Security Service